2009
DOI: 10.1158/1541-7786.mcr-08-0385
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids Down-Modulate CXCR4 Expression and Function in MDA-MB-231 Breast Cancer Cells

Abstract: Metastasis is the leading cause of death from breast cancer. A major factor of metastasis is the migration of cancerous cells to other tissues by way of up-regulated chemokine receptors, such as CXCR4, on the cell surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 46 publications
1
40
1
1
Order By: Relevance
“…Our data suggest DHA could prevent recruitment of the protein into lipid rafts from nonrafts as a consequence of the disruption in the spatial distribution of rafts (which may be occurring on several length scales). As another example, it was proposed that suppression of MDA-MB-231 breast cancer migration with (n-3) PUFA was due to an inability of the chemokine receptor CXCR4 to cluster, but the mechanism was not investigated (50). We propose a disruption in lipid rafts could prevent CXCR4 clustering and one approach would be to measure CXCR4 clustering with FRET imaging on a nanometer scale.…”
Section: Discussionmentioning
confidence: 96%
“…Our data suggest DHA could prevent recruitment of the protein into lipid rafts from nonrafts as a consequence of the disruption in the spatial distribution of rafts (which may be occurring on several length scales). As another example, it was proposed that suppression of MDA-MB-231 breast cancer migration with (n-3) PUFA was due to an inability of the chemokine receptor CXCR4 to cluster, but the mechanism was not investigated (50). We propose a disruption in lipid rafts could prevent CXCR4 clustering and one approach would be to measure CXCR4 clustering with FRET imaging on a nanometer scale.…”
Section: Discussionmentioning
confidence: 96%
“…Another well-known therapeutic target for BC metastasis is the chemokine receptor, CXCR4. Treatment of BC cells with DHA or EPA caused redistribution of CXCR4 from lipid rafts to the cell surface [105], resulting in an overall reduction in cell migration. In addition to shifting proteins out of lipid rafts, n -3 PUFA can prompt the localization of some proteins into these domains.…”
Section: N-3 Pufa Lipid Rafts and Breast Cancermentioning
confidence: 99%
“…ω−3 PUFAs also decreased the activity of the oncogenes ras and AP-1 downstream from the EGFR, which inhibited mitosis (Hardman, 2002). It has also been shown that ω−3 PUFA decrease membrane expression of the chemokine receptor CXCR4 in MDA-MB-231 breast cancer cells, which decreases their migration potential (Altenburg & Siddiqui, 2009). This appears to be due to the incorporation of ω−3 PUFAs into the cell membrane, which disrupts the cholesterol-rich lipid rafts that are required for CXCR4 dimerization and signaling through NF-κB (Wang et al, 2006).…”
Section: Anticancer Mechanisms Of ω−3 Pufasmentioning
confidence: 97%